How do the last five years measure up on levelling up? - Christine Farquharson; Luke Milsom; Imran Tahir; Bobbie Upton; Gautam Vyas (Institute for Fiscal Studies (IFS), 2024)
Five years ago, then Prime Minister Boris Johnson made "levelling up" a central plank of the Conservative Party's bid for re-election, with a manifesto pledge to "level up every part of the UK". In 2022, the government published a thorough and ambitious White Paper setting out 12 levelling up "missions" to achieve by 2030, as well as specific metrics by which they would be measured. In this report, we examine early progress towards those 12 missions, where possible using the headline metrics identified in the White Paper.
Keywords: 330; Business and investment; Education and skills; Employment and income; Health and social care; Poverty; inequality and social mobility; Distributional effects; Education; Employment; Firms; Further education; Geography; Government spending; Health; Housing; Human capital; Inequality; Innovation; Investment; Labour supply and workforce; Living standards